2006
DOI: 10.4314/gmj.v40i2.35986
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of trabeculectomies without adjunctive antimetabolites

Abstract: Trabeculectomy alone was effective in controlling IOPs to less than 22 mmHg in POAG. Lower IOP levels needed to control progressive visual field loss may require the use anti-metabolites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…This result is similar with different studies conducted by different authors at different time with different follow up period and population [18,19]. It is supported by the result reported by study conducted in Ghana which indicated that there was statistically significant difference between the mean pre-op and postop IOP (p=0.001) at the last examination at six months [20].…”
Section: Discussionsupporting
confidence: 90%
“…This result is similar with different studies conducted by different authors at different time with different follow up period and population [18,19]. It is supported by the result reported by study conducted in Ghana which indicated that there was statistically significant difference between the mean pre-op and postop IOP (p=0.001) at the last examination at six months [20].…”
Section: Discussionsupporting
confidence: 90%
“…3,4 In addition, previous studies have reported that between 22 and 26 percent of all patients operated for glaucoma at the Bawku Hospital in northeastern Ghana are below the age of 40 years. [6][7][8] However, despite these disturbing figures there is currently no nation-wide program to tackle the disease in the country. The study aims at determining the burden and presentation patterns of primary open angle glaucoma, using hospital-based data to highlight the need to develop nationwide intervention strategies to tackle the disease.…”
Section: Introductionmentioning
confidence: 99%
“…9 Similarly high success rates have been found in other studies among Black West African populations. 10,11 To the best of our knowledge, no prior study in Ghana has investigated the medical treatment as a sole modality for achieving AGIS target levels for IOP. The baseline IOP value reported in this study of 31.9 mmHg to the 6 th month value of 21.3 mmHg does not appear sufficient for adequate POAG control.…”
Section: Discussionmentioning
confidence: 99%